Applicability of Single Muscle CSA for Predicting Segmental Muscle Volume in Young Men - Tanaka, N. I.; Kanehisa, H. (International Journal of Sports Medicine, 2014)
The present study aimed to evaluate the applicability of using a single slice cross-sectional area (CSA) of the skeletal muscle for estimating segmental skeletal muscle volume (SMV). By using MRI, the SMV of each of the upper arm, lower arm, upper leg, lower leg, and trunk was determined in 29 males. First, step-wise multiple regression analysis was applied to develop the equation for each segmental SMV in which the CSAs at intervals of 10% of segment length (SL) were used as independent variables. Second, simple linear regression analysis with every CSA selected in the first step was applied to predict SMV in each body segment. In each segment, the standard error of estimate (SEE) in the simple linear regression equation was greater than that in the multiple regression one. The most appropriate slice level for measuring a single CSA to estimate SMV was 30% of the upper arm SL (R2=0.800, SEE=7.4%), 60% of the lower arm SL (0.788, 10.3%), 50% of the upper leg SL (0.795, 7.0%), and 20% of the trunk SL (0.813, 6.1%). For the lower leg, muscle CSAs at multiple slice levels are required to estimate SMV without the systematic error.
Keywords: cross-sectional area; skeletal muscle volume; estimation; magnetic resonance imaging method